Experimental Study on Resistance of Organic Material - Three-dimensional Planting Blanket on Loess Slope to Rainfall Erosion - YAO Kai; ZENG Kunxiang; ZHONG Yujian; REN Tong (Renmin Zhujiang)
Based on the self-developed loess-reinforced organic materials of Chengdu university of technology,and combined with ecological considerations,this paper proposes the organic material- three-dimensional planting blanket slope protection technology,analyzes the slope protection effects of organic materials and organic materials- three-dimensional planting blanket on loess erosion characteristics and slope runoff &sediment yield through artificial simulated rainfall test,as well as compares and evaluates the erosion resistance.The results show that:Organic materials can prevent the formation and development of rills on loess slopes,weaken the ability of slope runoff to erode the soil,and improve the slope stability;There is almost no erosion on three-dimensional planting blanket slope,so the slope stability is good;Under the same time,the runoff of the organic material slope is higher than that of the bare slope,while the cumulative runoff of the organic material- planting blanket slope is lower than that of the bare slope,and the total sediment yield of both is much smaller than that of the bare slope;The organic material- three-dimensional planting blanket slope protection is divided into two processes:in the first stage,the slope is protected and reinforced by organic materials,and in the later stage,the slope is mainly protected by three-dimensional planting blanket.Therefore,the combination of the two is more conducive to improving the resistance of loess to rainfall erosion.